Is Kinesio taping better than placebo taping for improving performance during unilateral vertical jump and hop tests? Protocol study for a randomized, placebo-controlled, double-blind, clinical trial - Glória, Igor Phillip dos Santos; Herpich, Carolina Marciela; Serenza, Felipe; Politti, Fabiano; Gonzalez, Tabajara de Oliveira; Gomes, Cid André Fidelis de Paula; Biasotto-Gonzalez, Daniela Aparecida (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Kinesio taping consists of the attachment of a thin elastic tape over specific muscles, the thickness of which is similar to that of the epidermis. This tape can be stretched to 140% of its original length, which demonstrates greater elasticity in comparison to conventional bandages. According to the creator of this method, Kinesio taping leads to better muscle activation or inhibition, reduces pain, swelling and muscle spasms and prevents muscle injury. Objective: The aim of the proposed study is to compare and analyze the immediate effect of Kinesio taping and placebo taping on performance during unilateral vertical jump and two hop tests by young professional soccer players. Methods: A randomized, placebo-controlled, double-blind, clinical trial will be conducted involving 100 athletes. The volunteers will be submitted to an evaluation of the dominant lower limb using the Single Leg Hop Test and Single Leg Triple Hop Test as well as the evaluation of a unilateral vertical jump on a pressure platform. The athletes will then be randomly allocated to two groups. Group A will receive Kinesio taping of the triceps surae muscle as described by Kase (2003, 2013) and Group B will receive a placebo taping of the same muscle. After 30 minutes, the volunteers will be submitted to the same evaluation tests. Analysis: Intra-group and inter-group analyses of the results will be performed. Statistical tests will be conducted considering a 5% significance level. This study is registered with Clinical Trials under protocol number: NCT02560961